Surveillance of Rotavirus Diarrhea in Dr. Hasan Sadikin General Hospital Bandung - Prasetyo, Dwi; Martiza, Iesje; Soenarto, Yati (Faculty of Medicine, Universitas Padjadjaran)
The diarrhea morbidity in Indonesia has increased, however, all the reports had not been done carefully, so that accurate surveillance are essential for improving quality of morbidity data. To determine the prevalence and clinical manifestations of rotavirus diarrhea and to characterize the circulating rotavirus strains, children below 5 years old who were admitted to Hasan Sadikin Hospital, Bandung because of diarrhea, from January 2006 through March 2007 were enrolled in a surveillance study and had stool specimens tested for the presence of rotavirus using enzyme immunoassay (EIA). The strains of rotavirus were determined using reverse transcriptase-polymerase chain reaction (RT-PCR). Rotavirus were detected in 47.8% analyzed samples (87/184), G and P-genotype of rotavirus were G[1] (37.5%) and P[6] (53.5%). Most subjects were males (56%), 6–11 months of age (35%). Most common clinical manifestations besides diarrhea were dehydration (72.7%) and vomiting (50%). Subjects with positive rotavirus more common had dehydration (72% vs 28%) and vomiting (61% vs 39%). In conclusion, vomiting and dehydration are the prominent clinical manifestations of diarrhea with positive rotavirus infection. G1 and P6 are the most common genotype of rotavirus. [MKB. 2010;42(4):155–60].Key words: Clinical manifestations, diarrhea, genotype, prevalence, rotavirus Surveilans Diare Rotavirus di Rumah Sakit Dr. Hasan Sadikin BandungMorbiditas diare di Indonesia meningkat, tetapi semua laporan belum dilakukan secara cermat, sehingga surveilans yang akurat penting untuk memperbaiki kualitas data. Penelitian ini dilakukan untuk menentukan prevalensi dan manifestasi klinis diare rotavirus serta karakteristik strain rotavirus, anak usia di bawah 5 tahun yang dirawat karena diare di RS Hasan Sadikin, Bandung, dari Januari 2006 sampai Maret 2007, diikutsertakan dalam suatu penelitian surveilans dan spesimen fesesnya diperiksa untuk mendeteksi adanya rotavirus dengan menggunakan enzyme immunoassay (EIA). Strain rotavirus diperiksa dengan reverse transcriptase-polymerase chain reaction (RT-PCR). Rotavirus terdeteksi pada 47,8% sampel analisis (87/184), genotipe-G dan P adalah G[1] (37,5%) dan P[6] (53,5%) dari strain. Kebanyakan subjek adalah laki-laki (56%) usia 6–11 bulan (35%). Manifestasi klinis terbanyak adalah dehidrasi (72,7%) dan muntah (50%). Subjek dengan rotavirus positif lebih sering mengalami dehidrasi (72% vs 28%) dan muntah (61% vs 39%). Simpulan, muntah dan dehidrasi adalah manifestasi klinis terbanyak pada diare dengan infeksi rotavirus. Genotipe G1 dan P6 merupakan genotipe rotavirus yang paling sering ditemukan. [MKB.2010;42(4):155–60].Kata kunci: Diare, genotipe, manifestasi klinis, prevalensi, rotavirus DOI: http://dx.doi.org/10.15395/mkb.v42n4.29